Invariantes aritméticos em geometria hiperbólica - Victor Mielly Oliveira Batista (2014)
In this dissertation we study some important arithmetic invariants associated with three-dimensional hyperbolic manifolds. They are the trace fields, invariant trace fields and the quaternions algebra. Well studied in particular Kleinian groups of finite covolume and find that your invariant trace field is a finite extension of the rational numbers. Wehave also developed the study of these invariants applied more generally to any nonelementary finitely generated subgroup of PSL(2;C).